2014
DOI: 10.1097/wno.0b013e3182a3060d
|View full text |Cite
|
Sign up to set email alerts
|

Sneddon Syndrome Presenting With Unilateral Third Cranial Nerve Palsy

Abstract: Sneddon syndrome is a rare systemic vasculopathy affecting the skin as livedo racemosa and the central nervous system as stroke. A 31-year-old man with a history of livedo racemosa presented with a partial left third nerve palsy. Skin biopsy showed signs of endotheliitis with obliteration of dermal blood vessels due to intimal proliferation and fibrin thrombi consistent with Sneddon syndrome. The patient was treated with platelet antiaggregant therapy with complete resolution of his third nerve palsy. Clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Rehany et al reported a young SS patient with internuclear ophtalmoplegia followed by ophthalmic artery occlusion [ 41 ]. Unilateral third cranial nerve palsy has been seen in a patient with SS and this is likely associated with microvascular complication [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehany et al reported a young SS patient with internuclear ophtalmoplegia followed by ophthalmic artery occlusion [ 41 ]. Unilateral third cranial nerve palsy has been seen in a patient with SS and this is likely associated with microvascular complication [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some diseases that can occur with generalized LR (such as SLE, polyarteritis nodosa, cryoglobulinemia, livedoid vasculitis, cold agglutinin disease, arteriosclerosis, cholesterin embolization and others [ 6 , 22 , 59 ]), must be excluded by appropriate clinical and laboratory tests. The differential diagnosis of neurological symptoms include multiple sclerosis, multiple embolization from cardiac source, infectious conditions (such as syphilis and lyme disease), and others [ 6 , 43 ]. Central nervous system (CNS) vasculitis refers to a broad array of diseases that result in inflammation and destruction of the blood vessels of brain, spinal cord and the meninges.…”
Section: Introductionmentioning
confidence: 99%
“…Sneddon syndrome is a non-inflammatory vasculopathy involving small- and medium-sized arteries. Sneddon syndrome involves various clinical features, including neurological and non-neurological symptoms [ 3 , 4 ]. The disease commonly affects women aged 20-40 years.…”
Section: Discussionmentioning
confidence: 99%
“…The disease commonly affects women aged 20-40 years. Multiple isolated familial cases were reported suggesting genetic causes [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Эти неспецифические симптомы в большинстве случаев предшествуют появлению сетчатого ливедо и серьезных неврологических изменений [14]. В литературе также были описаны экстрапирамидные расстройства в виде хореи или тремора в качестве манифестации синдрома Снеддона [36], а также поражение черепно-мозговых нервов [37].…”
Section: клиническая картина 1 сетчатое ливедоunclassified